The relationship between L2 instruction, exposure, and the L2 acquisition of a syntax–discourse property in L2 Spanish. (March 2019) - Leal, Tania; Slabakova, Roumyana
This article uses the clitic left dislocation (CLLD) construction in L2 Spanish to investigate whether generative SLA has valuable insights to contribute to language teaching. Although CLLD is a structure that is commonly used by native speakers, as reported anecdotally and in at least one corpus, we found that native-Spanish and native-English teachers of Spanish have little metalinguistic knowledge of it. Crucially, we also found that CLLD does not appear consistently in Spanish textbooks. Additionally, it appears to be infrequent in the classroom input that learners receive, as we found in three lectures we recorded and tallied for CLLD usage rates. At the same time, study results show that the construction is learnable. Study abroad, that is, exposure to naturalistic input, appears to be a significant factor. Based on these collective findings, we suggest that learners at intermediate proficiency levels should be exposed to CLLD and that generative SLA is valuable to teachers in identifying such gaps in instruction.